"No Body to be Kicked?" Monopoly, Financial Crisis, and Popular Revolt in 18th-Century Haiti and America - Ghachem, Malick W. (Law and literature, 2016)
Contemporary law and legal theory are resigned to the view that the corporation is a mere nexus of contracts, a legal person lacking both body and soul. This essay explores that commitment to the immateriality of the corporation through a discussion of the 18th-century revolt against the Indies Company in Saint-Domingue (Haiti) and British North America. Opponents of the joint-stock monopoly in these Atlantic settings believed, like critics of transnational corporate power today, that the company form represented a merger of wealth and power operating to subvert the liberties of disenfranchised outsiders. Financial crisis served to destabilize the fiscal and political environment that insulated the Indies Company from its critics, who took advantage of these openings by attacking the material embodiments of the corporation in the name of "free trade." The 18th-century opposition to monopoly privilege suggests that corporate personality was neither dismissed as fiction nor accepted as reality, and that in some circumstances, at least, the corporate body could indeed be held to account for the sins of a person without conscience.